Науковий туризм: досвід і перспективи - Ілляшенко, Сергій Михайлович; Ілляшенко, Наталія Сергіївна (ФОП Цьома С. П., 2024)
Викладено результати аналізу особливостей наукового туризму, як важливої складової успіху наукових конференцій. Окреслено складові успіху наукового туризму на наукових конференціях, які проводилися з фізичною присутністю учасників. Запропоновано рекомендації щодо формування комплексу заходів віртуального туризму як важливої складової наукового туризму конференцій, що проводяться за допомогою цифрових технологій віддаленого доступу.

The results of the analysis of the features of scientific tourism as an important component of the success of scientific conferences are presented. The components of the success of scientific tourism at scientific conferences, which were held with the physical presence of participants, are outlined. Recommendations on the formation of a set of virtual tourism activities as an important component of scientific tourism of conferences held with the help of digital technologies of remote access are proposed.
Scientific tourism: experience and prospects
Keywords: науковий туризм; діловий туризм; наукові конференції; складові успіху наукового туризму; віртуальний туризм; scientific tourism; business tourism; scientific conferences; components of the success of scientific tourism; virtual tourism